Using Eight Crops to Show the Correlation between Paucity Irrigation and Yield Reduction of Al-Hussainiyah Irrigation Project in Karbala, Iraq - Musa Habib Jassim Al-Shammari; Hayder Algretawee; Ali H. Al-Aboodi (Journal of Engineering)
Efficiency of water use in irrigation field always motivates researchers to find a way which could reduce irrigation quantity and obtain approximately the same crop yields. This study estimated the relationship between the paucity irrigation with the reduction in yield for eight crops (cotton, maize, alfalfa, small grain, summer vegetable, sesame, sunflower, and palms) by using various paucity irrigation stages from evapotranspiration of crops (5, 10, 15, 20, and 25%) as an indication of all crop outgrowth using medium soil. This study selected the project of Al-Hussainiyah irrigation that lies in Karbala province, which is close to Baghdad relative to the South. Also, the project has high importance because most dwellers have used the province for agriculture and drinking purposes. These are reasons of choosing it as a case study to implement paucity irrigation strategy on most crops (eight crops) within the project. The necessary records related to this study were obtained from specialized offices in Iraq, particularly water resources and agriculture ministries. Computer programs such as CROPWAT version 8.0, statistical program SPSS statistics version 20, and table curve 2D version 5.0 are considered the software for solving this model. This model was tested for its application and sensitivity by changing paucity levels for each crop. The comparison between the available and the estimated water demand showed that the paucity in irrigation water demand was very clear during the period from February to December for the average present state of agriculture. The correlation analysis gives a result that the paucity irrigation level with yield reduction manifested that the yield reduction rate of maize recorded higher than the other crops, while cotton recorded lower yield reduction rate than the other crops during all paucity stages.